2020
DOI: 10.1109/access.2020.2967453
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Functional Safety and Security Diagnosis Mechanism of CPS Based on Blockchain

Abstract: This paper proposes a functional safety and information security protection mechanism based on blockchain technology. The design of the basic level and integration level blockchain structure of CPS distributed architecture and related functional safety and information security measures are introduced. An effective communication judgment mechanism based on functional safety error threshold is proposed, which is stored and judged by smart contract. And a refund transaction with a clock is proposed to ensure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…IP packets are analyzed and consolidated to obtain source, destination IP, data volume, application protocol, and other information required. The advantage of doing so is that it does not change the network structure, increase the network load, or take up any network resources [ 16 ]. In other words, it is independent of the waiting time of the network and thus has no impact on the network usage by the users.…”
Section: Algorithm and Methodsmentioning
confidence: 99%
“…IP packets are analyzed and consolidated to obtain source, destination IP, data volume, application protocol, and other information required. The advantage of doing so is that it does not change the network structure, increase the network load, or take up any network resources [ 16 ]. In other words, it is independent of the waiting time of the network and thus has no impact on the network usage by the users.…”
Section: Algorithm and Methodsmentioning
confidence: 99%
“…The statistical results obtained on the reported risks in CPS from our studies show that the most reported impact of the identified risks consisted of (1) communication disruptions 57,105 , (2) system or sub‐system being compromised, 106,107 and (3) leading to system's abnormal behavior 108 and thus failure as a result of a malicious attack 109–111 . Another frequently reported impact is related to the physical aspect of the CPS and that is the equipment failure leading to financial losses, for example, Lopez et al 73 …”
Section: Findings Of Our Reviewmentioning
confidence: 76%
“…The mitigation measures proposed over the years range from physically placing security personnel guarding the system, 53 to controlling access to the system or data and 54 finally to integrating encryption schemes 55 ensuring confidentiality, authenticity, and integrity 56 of the data being transmitted between different components of the system. Most of the mitigation measures proposed over the years are driven either from exiting literature or internationally recognized standards introduced against the development of safety and security‐critical infrastructures 57 …”
Section: Related Workmentioning
confidence: 99%
“…After the competition, the selected vendors analyze the immutable product-in-use data maintained in blockchain to judge if the product has problems (Shahbazi and Byun, 2021a). An example is storing the functional integrity level and the stated functional error threshold in a smart contract and comparing the two parameters to judge if the product is blooey (Gu et al , 2020). If have, the vendors then explore what and where the problems are, otherwise they can predict the downtime of the product or its parts (Shahbazi and Byun, 2021b).…”
Section: Blockchain Applications In Smart Manufacturing Systemsmentioning
confidence: 99%